1993
DOI: 10.1002/zaac.19936191209
|View full text |Cite
|
Sign up to set email alerts
|

Isolierte [M6S14]‐Baueinheiten in ternären Sulfiden des Technetiums und Rheniums

Abstract: Durch Schmelzreaktionen von Alkalicarbonat mit elementarem Technetium oder Rhenium in einem mit Schwefel beladenen Wasserstoffstrom gelang die Darstellung der ternären Sulfide Rb10Tc6S14, Cs10Tc6S14, Rb10Re6S14 und Cs10Re6S14. Strukturuntersuchungen an Einkristallen ergaben, daß diese Verbindungen isotyp in der Raumgruppe Fm3m kristallisieren. Als charakteristische Strukturelemente treten [M6S14]‐Baueinheiten (M \documentclass{article}\pagestyle{empty}\begin{document}$ \hat = $\end{document} Tc, Re) auf, in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Under these constraints, it is a simple matter to enumerate the possible framework connectivities. A compilation of the 28 possibilities for general [M 6 Q 8 ] cluster frameworks is set forth in Table , along with some structurally proven examples. ,,,,,,, As one scans the table from top to bottom, the connectedness of the framework decreases from a maximum of 12 (with each core engaged in six rhombic M 2 Q 2 linkages) down to 0. The corresponding trend in the dimensionality of structured examples is much less unwavering…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under these constraints, it is a simple matter to enumerate the possible framework connectivities. A compilation of the 28 possibilities for general [M 6 Q 8 ] cluster frameworks is set forth in Table , along with some structurally proven examples. ,,,,,,, As one scans the table from top to bottom, the connectedness of the framework decreases from a maximum of 12 (with each core engaged in six rhombic M 2 Q 2 linkages) down to 0. The corresponding trend in the dimensionality of structured examples is much less unwavering…”
Section: Resultsmentioning
confidence: 99%
“…Over the years, a number of cluster phases have been structured featuring frameworks readily related by dimensional reduction. These phases, which were not previously correlated by the dimensional reduction argument, are collected in Table . , With the exception of Li 4 Re 6 S 11 , all of the parent phases (those of maximal dimensionality) have proven amenable to cluster excision, ,7b,8a rendering the dimensionally reduced products extraneous for purposes of cluster solubilization.…”
Section: Dimensional Reductionmentioning
confidence: 99%
“…Se, x = 12-13), were firstly reported by Bronger et al [16,17] Kryutchkov et al reported a bromide-capped cluster [Tc 6 (µ 3 -Br) 5 Br 6 ] 2-in which the eight capping sites were not fully occupied. [18][19][20] In this study, we report on several new chalcogenide-capped hexatechnetium(III) complexes that are expected to be the precursors for the synthesis of various hexatechnetium(III) complexes.…”
Section: Introductionmentioning
confidence: 69%
“…The Tc-Tc distances [2.609(1)-2.665(1) Å] and the Tc-Se distances [2.482(2)-2.509(1) Å], with the exception of Tc3-Se1, are similar to those of the reported selenide-coordinated hexatechnetium cluster Cs 4 Tc 6 Se 13 . [16] The distances between Tc3 and µ 4 -Se1 that are involved in the intercluster bridges [2.601(2) and [25] The polymeric structure [4] is shown in Figure 4. Complex [4] than the axial telluride.…”
Section: Crystal Structuresmentioning
confidence: 99%
“…Depending on the stoichiometry and synthesis conditions, most of the reported compounds present apical-apical bridges of sulfide S a-a or disulfide (S-S) a-a type extending along one to three directions [1,8,9]. An exception is the Cs 10 Re 6 S 14 compound, based on isolated cluster anion, with a very important negative charge [10].…”
Section: Ternary Compoundsmentioning
confidence: 99%